Phosphorus nutrition and mycorrhizal growth response of broadleaf and narrowleaf birdsfoot trefoils - Mendoza, Rodolfo Ernesto (2001)
In Argentina narrowleaf trefoil (Lotus glaber) predominates over broadleaf trefoil (Lotus corniculatus). Researchers have suggested this predominance occurs because L. glaber grows better at low levels of P availability. I studied the effect of increasing phosphorus (P) nutrition and mycorrhizal growth response of Lotus corniculatus and Lotus glaber in a soil of low available P. L. corniculatus was more efficient in P utilization than L. glaber and produced larger yields of shoot tissue per unit of P. The critical P concentration, measured as a percentage of P in the shoot required to achieve 90% of maximum shoot yield, was 0.22 in L. corniculatus and 0.28 in L. glaber. The roots of both two species were heavily infected by arbuscular micorrhizae (AM), and both mycorrhizal and nonmycorrhizal plants responded strongly to added P in soil. This suggests that both species are at no advantage or disadvantage whether mycorrhizal or nonmicorrhizal. The fraction of roots colonized by AM fungi differed between species at low levels of added P but was similar at high levels of added P. The specific root length (cm g-1) of mycorrhizal plants was greatest in L. corniculatus when P was insufficient to achieve maximum growth. The lower critical P concentration and the higher specific root length at low levels of P nutrition may be why L. corniculatus is superior to L. glaber in soils low in P. Therefore, the predominance of L. glaber compared with L. corniculatus in Argentinean soils is not due to ability of L. glaber to grow better in soil at low levels of P availability.